Development and Implementation of a Mobile Virtual Laboratory on Electrical Circuit Materials Using a Prophetic Integrated - Imas Ratna Ermawati; Acep kusdiweliran -; Martin - -; Syiffa Nurul Sya'adah; Berliani Amanda Diningsih (Jurnal Pendidikan Fisika dan Keilmuan (JPFK), 2022)
Development is research with the output of a product, either simply or structurally. Development research is used to design and produce a product systematically and meet the universal internal practicality criteria and use a scientific framework to realize physics education students, of course through a virtual laboratory that suits student needs. This study aims to develop an online-based practicum or e-learning using a virtual laboratory on electrical circuit material.This type of research uses Research and Development (R&D) using the Borg and Gall model. The sampling technique used is simple random sampling, which is a large-scale field trial of 18 students from Physics Education students, FKIP UHAMKA, East Jakarta. Data collection techniques using questionnaires, and documentation, while data analysis techniques using gain score test, quantitative and qualitative descriptive analysis. Model validation is carried out using expert judgment using the Delphi technique. The results of this study are (1) online/virtual laboratory practicum model; (2) development of an online/virtual laboratory electric circuit practicum with alternating current material; (3) the web-based student practicum model is feasible to apply. very good. The virtual laboratory is viewed from a prophetic perspective by using a questionnaire to measure student's prophetic during online practicums and collecting practicum assignments. The feasibility of using a virtual laboratory with an average value of 92% with good criteria when using a virtual laboratory is indicated by the overall average value for 4 (four) high-level user prophetic principles with a shidiq average of 8.64, Trustworthiness / responsibility with an average 9.08 average and tabligh/communicative with an average of 9.33 and fathonah/curiosity with an average of 8.67. The overall prophetic average was 8.93. The conclusion is that the electric circuit practicum through a virtual laboratory is feasible to train prophetically in student practicum on alternating current material.